Cooking Practices and Food Intake Pattern Amongst Adult Women in Pune City - Gothankar , Jayashree S; Patil , Reshma; Vaidya , Varsha M; Ghate , Mrunalini M (National Journal of Community Medicine, 2012)
Background: A Health exhibition was organized in Dhanakawadi, one of the drainage areas of a tertiary care Hospital in Pune city on women’s day 2008.Department of Community Medicine created a stall on the topic ‘Nutrition’. Since women in the family takes responsibility of cooking the food at household level, it is important to understand cooking and washing practices and promotion of healthy cooking practices amongst adult women. Objectives: To determine washing and cooking practices of women related to fruits, vegetables and rice and to elicit intake of different food groups by women. Methodology: Every alternate woman who visited the “Nutrition stall’ i.e 130 women were interviewed and a pre structured proforma was filled and women were then explained the charts which were displayed for the health exhibition. Results: Eighty percent women were up to the age of 50 years .Almost one third of women follow practice of washing fruits and vegetable after cutting .Eighty percent of women wash rice twice in excess of water which may lead to loss of water soluble vitamins. Seventy seven women use pressure cooker for cooking rice which is a good practice. Almost 71% of women have daily protein intake in the form of pulses and sprouts and almost one fourth women consume non vegetarian food 1-2 times per week. However fruits intake is low, only 28% consume fruits daily. 63 (almost 50%) women mix roasted soya bean grain in wheat grain before milling. Conclusion: Many women follow cooking practices which may lead to loss of vital nutrients like vitamin and minerals. Thus there is need for such health awareness programmes for women and adolescent girls on topics like healthy cooking practices.